Respostas

A melhor resposta!
2014-04-16T15:31:17-03:00
A) x^2-5x+6=0
Δ = (- 5)² - 4 × 1 × 6           X = - (- 5) +- √1  /  2 × 1
Δ = 25 - 24                        X = 5 +- 1  /  2
Δ = 1
x' = 5+1 / 2 => 6 / 2 = 3      x" = 5 - 1 / 2 => 4 / 2 = 2
S = {3,2}


b) x^2-8x+12=0
Δ = (- 8)² - 4 × 1 × 12        X = - (- 8) +- √16  /  2 × 1
Δ = 64 - 48                       X = 8 +- 4 / 2
Δ = 16
x' = 8+4 / 2 => 12 / 2 = 6    x" = 8-4 / 2 => 4 / 2 = 2 
S = {6,2}

c) x^2+2x-8=0
Δ = 2² - 4 × 1 × (-8)           X = - 2 +- √36  /  2 × 1
Δ = 4 + 32                        X = - 2 +- 6  /  2
Δ = 36
x' = -2+6 / 2 => 4 / 2 = 2     x" = -2-6 / 2 => -8 / 2 = -4
S = {2,-4}


d) x^2-5x+8=0
Δ = (- 5)² - 4 × 1 × 8
Δ = 25 - 32                         Não tem Solução, pois não há raiz de números negativos.
Δ = - 7
1 5 1